2010
DOI: 10.2478/10004-1254-61-2010-2065
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal, Early Life, and Childhood Exposure to Genotoxicants in the Living Environment

Abstract: Health disorders and diseases related to environmental exposure in children such as cancer and immunologic disturbances (asthma, allergies) are on the rise. However, complex transplacental and prepubertal genotoxicology is given very limited consideration, even though intrauterine development and early childhood may be critical for elucidating the cancer aetiology. The foetus is transplacentally exposed to contaminants in food and environment such as various chemicals, drugs, radiochemically contaminated water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 97 publications
0
14
0
2
Order By: Relevance
“…Potential sources of metal exposure include groundwater contamination, metal working, leather tanning, and mining [1][2][3][4]. In addition to environmental and occupational settings, a variety of uses in medicine can result in exposure to different forms of metals [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Potential sources of metal exposure include groundwater contamination, metal working, leather tanning, and mining [1][2][3][4]. In addition to environmental and occupational settings, a variety of uses in medicine can result in exposure to different forms of metals [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the general health effects on adults, it has also been shown that cigarette smoking effects unborn babies, as well as children who are exposed to tobacco smoke as passive smokers (1)(2)(3). Epidemiological data (2,4) show that tobacco smoke is associated with detrimental effects on foetal growth, low birth weight and preterm deliveries.…”
mentioning
confidence: 99%
“…It is well-documented that cigarette smoke is a threat to general health with specific and direct consequences in the form of heart and pulmonaryrelated diseases and various cancers (1)(2)(3). Apart from the general health effects on adults, it has also been shown that cigarette smoking effects unborn babies, as well as children who are exposed to tobacco smoke as passive smokers (1)(2)(3).…”
mentioning
confidence: 99%
“…Indoor climatic conditions, structural deficiencies and physical shortcomings may be salient aspects of housing quality for psychological health (Evans et al , ; Evans et al , ). In addition, exposure to secondary tobacco smoke may be a risk factor for children's healthy development (for a review, see Katic et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Indoor climatic conditions, structural deficiencies and physical shortcomings may be salient aspects of housing quality for psychological health (Evans et al, 2000;Evans et al, 2003). In addition, exposure to secondary tobacco smoke may be a risk factor for children's healthy development (for a review, see Katic et al, 2010). The television is on in the residence (-) Note: Values are factor loadings and communalities (h 2 ) for EFA using geomin rotations in 3406 families.…”
Section: Exploratory Factor Analysis (Efa)mentioning
confidence: 99%